Pengaruh Beban Pajak Tangguhan, Perencanaan Pajak dan Penghindaran Pajak Terhadap Manajemen Laba pada Perusahaan Barang Konsumsi Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Vanesa Azhara; Idel Eprianto; Amor Marundha (Mulia Pratama, 2023)
This study examines the Effect of Deferred Tax Expenses, Tax Planning and Tax Avoidance are equally influential with the dependent variable, Earnings Management. The population in this research is a food and beverage consumer goods company registered at Indonesia Stock Exchange for the 2018-2020 period. Data collection techniques in this study were carried out using library research and documentation and obtained as many as 30 data samples. The analytical method used is Multiple Linear Regression. The study results show that Deferred Tax Expenses have a negative effect on Profit Management, and Tax Planning has a positive effect on Profit Management. Tax Avoidance has a negative effect on Profit Management, and Deferred Tax Expenses, Tax Planning, and Tax Avoidance have a combined effect on the dependent variable, namely Profit Management.